Progress towards the experimental reintroduction of woodland caribou to Minnesota and adjacent Ontario - Jordan, Peter A.; Nelson, James L.; Pastor, John (Rangifer, 1998)
Woodland caribou (Rangifer tarandus caribou) are native to Minnesota but started to decline in the mid 1800s and disappeared from the state by 1940. Their demise had been attributed to extensive timber harvest and ovethunting; but more recently mortality from the meningeal worm, Parelaphostrongylus tenuis, carried by white-tailed deer (Odocoileus virginianus), and increased prédation by timber wolves (Canis lupus) and black bears (Ursus americanus) have been suggested as additional causes. We describe a current initiative to explore feasibility of restoring caribou to the boundary waters region of Minnesota and Ontario. Feasibility studies have been conducted under the guidance of the North Central Catibou Corporation (NCCC), a non-governmental organization with representation from relevant state, federal, Native American, and Canadian agencies. Results indicate a) Within Minnesota the most suitable site for woodland caribou lies within the eastern sector of the Boundary Waters Canoe Area Wilderness (BWCAW), and this is contiguous with a similarly suitable sector of Ontario's Quetico Provincial Park: Together these comprise the recommended 1300-km2 Boundary Waters Caribou Region (BWCR); b) Vegetation in the BWCR has changed little since the 1920s when caribou were last present other than effects of fire suppression; c) Level of white-tailed deer, hence the meningeal worm, is so low in the BWCR that this factor is unlikely to impede survival of re-introduced caribou; d) While wolf numbers within the wider region are relatively high, their impacts may be minimized if caribou are released in small, widely scattered groups; in addition, an abundance of lakes with islands affords good summer-time prédation security; e) Threat to calves from black bears, probably more numerous than in earlier times, appears lessened by the security of lakeshores and islands; and f) A simulation model, combining knowledge from elsewhere with the BWCR assessment, suggests that released animals have a 0.2 to 0.8 chance of increasing in numbers during the first 20 years post-release. Strategies for maximizing success are identified. NCCC has concluded that the only practical approach that remains for determining restoration feasibility is through experimental releases or caribou. While promise of eventual success appears only moderate, the NCCC feels that costs and uncertainties associated with the experiment are justified by the environmental benefits from a success. Even if the effort fails, valuable knowledge would accrue for conservation biologists in general. An action plan is outlined, and progress and problems in selling the caribou initiative are discussed.